Nucleoporin 54 contributes to Homologous recombination repair and post-replicative DNA integrity - Rodriguez-Berriguete, G; Granata, G; Puliyadi, R; Tiwana, G; Prevo, R; Wilson, R; Yu, S; Buffa, F; Humphrey, T; McKenna, W; Higgins, G (Oxford University Press, 2018)
The nuclear pore complex (NPC) machinery is emerging as an important determinant in the maintenance of genome integrity and sensitivity to DNA double-strand break (DSB)-inducing agents, such as ionising radiation (IR). In this study, using a high-throughput siRNA screen, we identified the central channel NPC protein Nup54, and concomitantly its molecular partners Nup62 and Nup58, as novel factors implicated in radiosensitivity. Nup54 depletion caused an increase in cell death by mitotic catastrophe after IR, and specifically enhanced both the duration of the G2 arrest and the radiosensitivity of cells that contained replicated DNA at the time of IR exposure. Nup54-depleted cells also exhibited increased formation of chromosome aberrations arisen from replicated DNA. Interestingly, we found that Nup54 is epistatic with the Homologous Recombination (HR) factor Rad51. Moreover, using specific DNA damage repair reporters, we observed a decreased HR repair activity upon Nup54 knockdown. In agreement with a role in HR repair, we also demonstrated a decreased formation of HR-linked DNA synthesis foci and sister chromatid exchanges after IR in cells depleted of Nup54. Our study reveals a novel role for Nup54 in the response to IR and the maintenance of HR-mediated genome integrity.